Effectiveness of the Antenatal Training Program on Reducing Anxiety and Pain Levels in Mothers During Gestation at the Sobang Community Health Center in 2024 - Lia Idealistiana; Fia Oktapiani; Yanah; Evi Cahya Wulandari (Jurnal Penelitian Pendidikan IPA, 2024)
Women often experience anxiety and fear during pregnancy due to concerns about the pain of childbirth. This anxiety can lead to mental and physical tension, resulting in unnatural stiffness in muscles and joints. Such stress is associated with negative pregnancy outcomes, mood disturbances, and various somatic complaints. Physical exercise during pregnancy can be an effective intervention to reduce anxiety and pain, benefiting both maternal and fetal health. This study aimed to evaluate the effectiveness of the Antenatal Training Program in reducing anxiety and altering pain perception during pregnancy. The research involved 30 pregnant women at the Sobang Community Health Center, Pandeglang Regency, who completed pre-test and post-test questionnaires. The study results showed a significant improvement (p < 0.05) in reducing anxiety and pain perception among participants, confirming the effectiveness of antenatal exercise. The findings suggest that consistent participation in antenatal exercises positively impacts the childbirth experience. Additionally, pregnant women are advised to maintain proper nutrition and monitor their activities to ensure a healthy pregnancy and delivery activities carried out during the gestation period.